Legal Review of Perpetrators of Schizophrenic Psychiatric Disorders (Legal Review of Article 44 of Law Number 1 of 2023 In The Crime of Murder) (Case Study Decision Number: 181/Pid/2024/PT DKI) - Anggarita, Levy Rizka; Sumampouw, Wuri; Asyharuddin, Asyharuddin (JIHAD : Jurnal Ilmu Hukum dan Administrasi, 2025)
(1) Schizophrenia is a serious mental disorder in which the sufferer has difficulty distinguishing between delusion and reality. This condition is commonly characterized by unusual behaviors such as delusions and hallucinations. For this reason, individuals experiencing such symptoms are often referred to as "insane," though the term carries stigma and oversimplification. (2) This research employs a normative juridical approach, specifically using the statute approach and the case approach. The writer also applies a qualitative descriptive analysis method to provide a comprehensive understanding of the phenomena under study. (3) The murder case involving Andi Andoyo in Decision Number 181/Pid/2024/PT DKI attracted public attention due to the involvement of a perpetrator diagnosed with paranoid schizophrenia. Despite medical evidence and expert testimony confirming a severe mental disorder, the panel of judges sentenced the defendant to 16 years in prison. In fact, Article 44 of the Indonesian Penal Code (KUHP) provides legal space for individuals with mental disorders to be rehabilitated rather than punished with imprisonment. This highlights the importance of substantive justice and the need for a more sensitive judicial system toward the mental condition of defendants. (4) Article 44 of Law Number 1 of 2023 concerning the Criminal Code allows for mentally ill offenders to be exempt from punishment and placed in a mental hospital. This is also in line with Law Number 17 of 2023 concerning Health, which affirms the right of individuals with mental disorders to receive medical care and rehabilitation. When medical aspects are ignored in legal considerations, achieving substantive justice becomes increasingly difficult.